If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 17 + -3x + 2 = 28 + 2x + -1x Reorder the terms: 17 + 2 + 5x + -3x = 28 + 2x + -1x Combine like terms: 17 + 2 = 19 19 + 5x + -3x = 28 + 2x + -1x Combine like terms: 5x + -3x = 2x 19 + 2x = 28 + 2x + -1x Combine like terms: 2x + -1x = 1x 19 + 2x = 28 + 1x Solving 19 + 2x = 28 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 19 + 2x + -1x = 28 + 1x + -1x Combine like terms: 2x + -1x = 1x 19 + 1x = 28 + 1x + -1x Combine like terms: 1x + -1x = 0 19 + 1x = 28 + 0 19 + 1x = 28 Add '-19' to each side of the equation. 19 + -19 + 1x = 28 + -19 Combine like terms: 19 + -19 = 0 0 + 1x = 28 + -19 1x = 28 + -19 Combine like terms: 28 + -19 = 9 1x = 9 Divide each side by '1'. x = 9 Simplifying x = 9
| -3(x+4)-9=14 | | 6.4+2.1(a-2)=8.5 | | 9-22= | | -x-2(7)=-15 | | 4x^2-50x+114=0 | | -13-14= | | x-2(7)=-13 | | .13(d+6)=1.95 | | -6+7+-3+3= | | 6x+5(4x-5)=27 | | 6x-2(3x+2)=-4 | | -3(3m-6)=2m+18 | | x^2-5x-1= | | log^3x=2 | | 3x-7+4x=29 | | .7(3+n)=14.7 | | 5(k+1)-k=3(k+2) | | -6+(-9)= | | -25-6a=-4(1+6a)-3 | | 5y=12-9y | | -9(y+1)=-9 | | 4(-6)-2y=-22 | | 14+(-15)= | | Y=Z-4x | | -.25(n+5)=2 | | F(1.5)=3x-2 | | 4a+3(2a+4)=24 | | -5p+7(3p+7)=-39-6p | | 8(2n-5)=-1/2(6n-2) | | .375b+18=-2.25 | | -19+-6= | | 0.7n+5.4=-1.6 |